レビー小体型認知症への作業療法評価に関する文献レビュー - 佐々木 智也; 石橋 裕 (作業療法, 2024)
要旨：レビー小体型認知症（以下，DLB）はパーキンソン病（以下，PD）と同一の機序で起こり，類似した症状が出現する．PDは作業療法ガイドラインで一定の評価指標が推奨されているが，DLBに関しては報告が少なく評価の実施状況は不明である．そこで，DLBへの作業療法介入における評価指標を明らかにすることを目的に，DLBへ介入を行った研究の文献レビューを行い，用いられた評価指標を調査した．結果14件の論文が採用され，認知機能，作業，日常生活動作の評価が実施されている現状が明らかになった．一方，PDと比較して身体機能，精神機能，疾患特異性の評価が不十分で，評価指標を用いることで障害や強みを多面的に捉えられる可能性がある． 　Dementia with Lewy bodies (DLB) occurs through the same mechanisms as Parkinson's disease (PD）, leading to similar symptoms. While PD occupational therapy guidelines recommend several assessment indicators, there have been few reports on DLB, and the status of assessments is unclear. Therefore, to elucidate the assessment indicators in occupational therapy interventions for DLB, we conducted a literature review of occupational therapy intervention studies targeting DLB and examined the assessment indicators used. As a result, 14 papers were included, revealing that assessments of cognitive function, tasks, and activities of daily living are being conducted. However, compared to PD, assessments of physical function, mental function, and disease-specific evaluations are insufficient. Using assessment indicators may allow for a multifaceted understanding of disabilities and strengths.